The Language Environment Strategy for Developing Language Skills Based on the Communicative Approach - Lutfiani, Yuni; Sanah, Siti; Nugraha, Dadan (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study explores the implementation of the biah lughawiyah (language environment) strategy in developing four Arabic language skills at the Bandung Arabic Boarding School. Employing descriptive qualitative methods, data were collected through observation, interviews, and documentation. The findings reveal two types of biah lughawiyah: formal and informal. The formal environment focuses on structured activities for listening, speaking, reading, and writing, while the informal environment includes various linguistic activities such as vocabulary exercises, Arabic movie watching, language days, and competitions. The strategy predominantly emphasizes speaking skills, aligning with the principles of communicative Arabic learning in the 21st century. This research offers insights into biah lughawiyah development and serves as a foundation for further studies in this area.